Effect of storage methods on willow chips quality. (September 2016) - Krzyżaniak, Michał; Stolarski, Mariusz J.; Niksa, Dariusz; Tworkowski, Józef; Szczukowski, Stefan
Abstract: Lignocellulose biomass is a key source of bioenergy in the EU and in Poland. Therefore, this study analysed the effect of the method of storing chips obtained from short rotation willow on their thermophysical and chemical properties and on the biomass loss, depending on the method of storage and the type of cover, in the climatic conditions of Central-Eastern Europe. The experiment involved examination of five methods of storage of willow chips: with no cover (control), under permeable covers Toptex 200 and Toptex 300, under vapour-permeable foil and in a wooden shed. The chips were stored from March 2011 to March 2012. Use of cover made of permeable materials was found to improve the biomass quality: its moisture content decreased more than twice and its heating value increased more than twice. The energy content of the stored piles was also found to increase by 10% after a year of storage. The energy content was also found to increase in a roofed pile and to decrease in biomass covered with foil (−9%) and uncovered (−50%). Biomass loss for chips stored under permeable covers ranged from 3.8% to 5.1%. Similar findings were recorded for chips stored in a shed, while the effects were worse for the piles stored under vapour-permeable foil. The worst biomass parameters were recorded for an uncovered pile. Storage of willow chips in an open space under cover could be a cheaper alternative, which could improve the quality of willow chips compared to roofed warehouses. Highlights: Willow wood chips were stored under different covers for a year. Permeable membranes decreased willow chips moisture content more than twice. Energy content was high in piles stored under Toptex and in a shed (17.14–17.68 GJ). The smallest loss of dry biomass was found for Toptex 200 (3.84%). The highest loss of dry biomass was found for biomass in control (41%).